Progress report from the AMAP Board to the SAO Meeting in Selfoss, Iceland, May 4-5, 2004. - Arctic Monitoring and Assessment Programme (AMAP) (Arctic Monitoring and Assessment Programme (AMAP), 2004)
"AMAP is following the approved work plan for the period 2003-2004 as outlined in the SAO report to Ministers, Ivalo 2002. The main task for AMAP during this period is to produce the ACIA scientific assessment and overview report, to be presented to the Ministerial meeting in 2004. This has been a joint work with CAFF and IASC. The Scientific and Overview reports are intended to be signed-off by the scientists, the AMAP and CAFF WG and IASC by the end of June. A detailed report will be presented at the SAO meeting." /./